2021
DOI: 10.1111/aor.13886
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis‐related headache: Still a challenge in 2020? Effect of conventional versus online hemodiafiltration from a study in Casablanca, Morocco

Abstract: Hemodialysis‐related headache (HRH) is a well‐known clinical event. It is considered as one of the most commonly reported neurological symptoms among hemodialysis patients. Its epidemiological, physiological, clinical, and therapeutic data remain scarce and are poorly studied. Our aim was to determine the frequency of HRH in the region of Casablanca, Morocco, to describe its clinical characteristics and to explore the hypothesis that renal replacement techniques, such as conventional versus online hemodiafiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The current study revealed a relatively low incidence of HRH compared to prior investigations, which might be attributed to variations in the observation period and advancements in dialysis techniques and prescriptions in recent years [ 1 7 ]. Despite the significant association between HRH and a lower quality of life [ 14 ], there exists no consensus on its treatment due to its diverse and complex causes [ 1 6 ].…”
Section: Discussionmentioning
confidence: 53%
“…The current study revealed a relatively low incidence of HRH compared to prior investigations, which might be attributed to variations in the observation period and advancements in dialysis techniques and prescriptions in recent years [ 1 7 ]. Despite the significant association between HRH and a lower quality of life [ 14 ], there exists no consensus on its treatment due to its diverse and complex causes [ 1 6 ].…”
Section: Discussionmentioning
confidence: 53%
“…In ICHD-3, the diagnostic criteria for 10.2 HDH did not describe the clinical characteristics of headache. We summarised the clinical characteristics of HDH in the previous literature and our own research, which are shown in Table 4 [ 3 , 5 , 8 , 14 17 ], and discovered that HDH has some common characteristics, such as moderate intensity and bilateral frontal-temporal lobe, with a mean duration of less than 4 h. Therefore, it is suggested to add a diagnostic criteria D: “ Headache has one of the following characteristics:1) moderate intensity, 2) located at bilateral frontal-temporal lobe, 3) the mean duration less than four hours. ” Based on the above discussion, we recommend Table 5 as 10.2 new diagnostic criteria for dialysis headaches.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus regarding the pathophysiology or triggering factors of headache during haemodialysis (HDH). Factors associated with dialysis headaches include sodium ion, magnesium ion [ 6 ], urea, blood pressure changes, and weight levels; calcitonin gene-related peptide and substance P levels during dialysis [ 7 ]; and different haemodialysis (HD) modalities (standard HD and online hemodiafiltration technique (OL-HDF), standard HD presents a higher risk of dialysis headache than OL-HDF) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Morocco suggested that renal replacement therapy like online hemodiafiltration gave superior results in terms of reduced incidence of HDH. [ 16 ] Further studies assessing how dialysis strategies can change frequency and severity of HDH would be required. We also evaluated the different modalities of treatment used by patients for treatment of HDH.…”
Section: Discussionmentioning
confidence: 99%